An Efficient Stereoselective Total Synthesis of All Stereoisomers of the Antibiotic Thiamphenicol through Ruthenium‐Catalyzed Asymmetric Reduction by Dynamic Kinetic Resolution. Issue 27 (14th July 2015) - Perez, Marc; Echeverria, Pierre‐Georges; Martinez‐Arripe, Elsa; Ez Zoubir, Mehdi; Touati, Ridha; Zhang, Zhaoguo; Genet, Jean‐Pierre; Phansavath, Phannarath; Ayad, Tahar; Ratovelomanana‐Vidal, Virginie
Abstract: Thiamphenicol is a widely used antibiotic that exhibits activity against numerous Gram‐positive and Gram‐negative pathogens. Here, we describe the expedient synthesis of its four stereoisomers through a dynamic kinetic resolution that follows a ruthenium‐catalyzed asymmetric hydrogenation or a hydrogen transfer reaction as the key step. Abstract : An expedient synthesis for the four isomers of the broad‐spectrum antibiotic thiamphenicol is described through either a ruthenium‐catalyzed asymmetric hydrogenation or a transfer hydrogenation reaction by a dynamic kinetic resolution.